2014
DOI: 10.1177/0954008314561806
|View full text |Cite
|
Sign up to set email alerts
|

Studies on structurally different benzoxazines

Abstract: Bisbenzoxazines were prepared by the condensation of the respective bisphenols bisphenol A (BA), indane bisphenol (IBP), and spirobiindane bisphenol (SBI) with paraformaldehyde and aniline. The apparent activation energies for the polymerization curing process ( Ea-C) and the degradation process ( Ea-D) were calculated using Flynn–Wall–Ozawa, Vyazovkin, and Friedman methods. The variation in Ea-C noted for the thermal curing of different bisbenzoxazines is attributed to the operation of different mechanisms fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…Considering the polymerization mechanisms and the intimate structures of poly(FAEN-Bz), the thermal decomposition processes can be concluded as follows (shown in Scheme 3): firstly, the Mannich bridge was broken and the long molecular structures of poly(FAEN-Bz) turn into aromatic ester nitrile segments, which possessed outstanding thermal stability (Scheme 3a) [9]. At the elevated temperatures, the segments began to collapse along with the fracture of chemical bonds (Scheme 3b) [27].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering the polymerization mechanisms and the intimate structures of poly(FAEN-Bz), the thermal decomposition processes can be concluded as follows (shown in Scheme 3): firstly, the Mannich bridge was broken and the long molecular structures of poly(FAEN-Bz) turn into aromatic ester nitrile segments, which possessed outstanding thermal stability (Scheme 3a) [9]. At the elevated temperatures, the segments began to collapse along with the fracture of chemical bonds (Scheme 3b) [27].…”
Section: Resultsmentioning
confidence: 99%
“…It has been widely used in construction, electronics, aerospace and other fields [8]. However, traditional phenolic resin often releases volatiles which corrode the processing equipment during the curing process [9]. It will lead to the formation of micro-voids, and damage the performance of final materials.…”
Section: Introductionmentioning
confidence: 99%
“…This restricts the motion of oxazine rings, leading to less involvement of oxazine rings in polymerization and, therefore, resulting in lower ∆H values [192]. Incorporation of rigid spacer units, trimethylphenyl indane and tetramethyl spirobiindane between the reactive benzoxazine units, leads to mobility restriction imposed on the reactive sites by the increasing viscosity of the polymerizing medium, affecting the polymerization rate [401]. The effect of intermolecular H-bonding between the urea linkages allowed close proximity of oxazine rings, which in turn, lead to accelerated polymerization at much lower temperature [225].…”
Section: Acceleration Of the Rate Of Polymerization Via Intramolecular Interaction 41 Modification Of Monomer Structures By Electron-donamentioning
confidence: 99%
“…This increase in E a and the increase in conversion rate for stages 1 and 2 have already been described by researchers. Shamim Rishwana et al 52 have observed that the CN bond, with its relatively low energy of 305 kJ/mol in contrast to the CC bond (346 kJ/mol), undergoes its degradation during the early phases of degradation, specifically at lower conversion degrees. Consequently, Schiff base products are generated as a result.…”
Section: Resultsmentioning
confidence: 99%